The usborne illustrated dictionary of physics - Wertheim, Jane; Oxley, C. Stockley, C. Johnson, Fiona (Usborne London, 2011)
This is a new edition of this popular title, which provides a fantastic reference point for students studying for their SATs and GCSE's. Split into 6 colour coded sections covering all aspects of the curriculum, such as radioactivity, heat, sound and electricity, as well as a general information section which includes essential charts and tables, it is brightly and clearly illustrated. It is internet-linked to further online educational resources through the Usborne Quicklinks website